Pemanfaatan Sampah Organik Rumah Tangga Menjadi Pupuk Kompos Dalam Meningkatkan Peduli Lingkungan Di Desa Patimban - Tita Kartika Dewi; Deny Ernawan; Deden Robi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
The purpose of this service is to provide education to the public regarding the Utilization of Household Organic Waste to Become Compost Fertilizer in Increasing Care for the Environment. The method used the method in writing this article uses a qualitative approach with a descriptive-explanative model which intends to provide a detailed description of the work program for making compost, including by raising awareness, counseling or short lectures and demonstrating how to make compost. Adpaun as a result of community awareness activities for the environment has increased, especially in organic waste which is used as compost. This can be seen from the many questions asked by the people who participated in the extension activities. The community gains insight into the manufacture and benefits of compost from organic waste which is accelerated with the help of an EM4 (effective microorganism) activator. The finished organic compost can be used by the community to be an alternative to chemical fertilizers or fertilizer from factories, a substitute for planting media, and if it can be produced on a large scale or en masse, it will have additional value. The creation of a community environment that is clean, healthy and cares about health both personally and for the environment.